Physiological factors to predict on traditional rowing performance - Izquierdo-Gabarren, M.; Gonzalez de Txabarri Exposito, R.; Saez de Villarreal, E.; Izguierdo, M. (European Journal of Applied Physiology, 2010)
The purpose of this study was to determine the best prediction factors of traditional rowing performance in traditional elite (ER) and amateur (AR) rowers. Average power during the 20-min all-out test (W 20 min), average power output which elicited a blood lactate concentration of 4 mmol l-1 ( W4 \textmmol \textl - 1 ), W4mmoll-1 power output in 10 maximal strokes (W 10 strokes), maximal strength and muscle power output during a bench pull (BP) and anthropometric values were all measured for 46 trained male rowers aged 21-30 with 8-15 years of rowing training experience. The ER group showed greater body mass (5%, p < 0.05), greater fat free body mass (5%, p < 0.05), greater 1RMBP (13%, p < 0.001), longer training experience (43%, p < 0.001), and a shorter time in the 2,000 m test (4%, p < 0.05) than the AR group. The ER group showed higher power output values in W 10 strokes (9%, p < 0.01), W 20 min (15.4%, p < 0.01) and W4 \textmmol \textl - 1 W4mmoll-1(17.8%, p < 0.01) compared with the AR group. Significant relationships were observed between W4 \textmmol \textl - 1 W4mmoll-1and W 20 min (r = 0.65 and 0.80; p < 0.01 in ER and AR, respectively). The indices for rowing performance suggested that W 20 min, W4 \textmmol \textl - 1 , W4mmoll-1W 10 strokes and 1RMBP were the most important predictors of traditional rowing performance in elite and amateur rowers.